THE EFFECT OF THE INTERVAL TIME IMMERSION IN THE NATURAL FEED TANK OF Chaetoceros simplex ON GROWTH AND SURVIVAL RATE OF PEARL OYSTER (Pinctada Maxima) - Septiani, Ninda; Amir, Sadikin; Mukhlis, Alis (Aquaculture Department, University of Mataram, 2023)
Pearl oysters are a fishery commodity with a high economic value because all parts of its body have a sale value. However, many problems of pearl oyster hatcheries are low survival rates and pearl oyster growth is not uniform. The research objective is to determine the effect of the interval time immersion in the natural feed tank in the feed concentrate of Chaetoceros simplex and to determiinterval time best immersion is duced the grey growth and survival rate of (Pinctada maxima). The method in this research is the experimental method and with a completely randomised design (CRD), with five treatments andthree3 replications. The A treatment) : control/without immersion, B (Interval time 24 hours immersion every one day, C (Interval time 48 hours immersion every two days, D (Interval time 72 hours): Immersion every three days and E treatment (Interval time 92 hours): immersion-furry for four days. The research result is interval time immersion spat of pearl oysters in the natural feed tank significantly affects the shell growth of the dorso ventral of pearl oyster Pinctada maxima (p<0,05). The highest growth was achieved in treatment B with an absolute growth value of 1.68 mm, a relative growth of 122,06% from the initial size, and a daily specific growth rate of 0,59% per day.